2021
DOI: 10.1093/ons/opab332
|View full text |Cite
|
Sign up to set email alerts
|

Supralesional Ablation Volumes Are Feasible in the Posterior Fossa and May Provide Enhanced Symptomatic Relief

Abstract: BACKGROUND Laser interstitial thermal therapy (LITT) for posterior fossa lesions remains rare as the small size of the infratentorial compartment, proximity to the brainstem, and thickness/angulation of the occipital bone creates barriers to procedural success. Furthermore, evaluation of the effect of ablation volume on outcomes is limited. OBJECTIVE To analyze our institutional experience with LITT in the posterior fossa str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…One study reported only the diameters of the lesions on posterior fossa and was also excluded in pre-LITT volume’s measurement [ 17 ]. Three studies reported pre- and postprocedural KPS scores, with a combined mean score of 90 pre-LITT and 80 post-LITT for 38 patients [ 12 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study reported only the diameters of the lesions on posterior fossa and was also excluded in pre-LITT volume’s measurement [ 17 ]. Three studies reported pre- and postprocedural KPS scores, with a combined mean score of 90 pre-LITT and 80 post-LITT for 38 patients [ 12 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morbidity and mortality data could be extracted for 131 of the 150 patients included in this study. Nine deaths (9/131) resulted from disease progression, treatment failure, or metastasis, and no death occurred from LITT treatment [ 11 , 25 ]; 103 patients had no procedural complications and showed stabilization of disease at the time of last follow-up, which ranged from 2 to 24 months [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 23 , 25 ]; and 19 patients developed intra- or postoperative complications, including transient and permanent neurologic deficits [ 11 , 12 , 14 , 21 , 23 , 25 ]. Procedure-related complications, usually including new neurologic deficits, occurred in approximately 14.5% (19/131) of the pooled sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations